A highly sensitive LC-MS/MS method for the determination and quantification of a recently identified N-nitrosamine impurity in the sitagliptin phosphate monohydrate active pharmaceutical ingredient. Issue 3 (4th January 2023) - Wang, Zhen; Hu, Shujun; Wu, Xiaoying; He, Zuwei; Ke, Chunlong; Hu, Miaomiao
Abstract : A fully validated LC-MS/MS method was developed for quantification of 7-nitroso-3-(trifluoromethyl)-5, 6, 7, 8-tetrahydro-[1, 2, 4]triazolo[4, 3-a]pyrazine (NTTP) in sitagliptin phosphate monohydrate at LOQ of 0.098 ppm. Abstract : A liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was used for the quantification of 7-nitroso-3-(trifluoromethyl)-5, 6, 7, 8-tetrahydro-[1, 2, 4]triazolo[4, 3- a ]pyrazine (NTTP) in the sitagliptin phosphate monohydrate active pharmaceutical ingredient. Chromatographic separation was achieved using an Agilent-ZORBAX SB-C18 column, with 0.01 mol L −1 ammonium formate in water as mobile phase A and acetonitrile as mobile phase B in gradient elution mode at a 0.4 mL min −1 flow rate. Quantification of impurities was carried out using triple quadrupole mass detection with electrospray ionization in the multiple reaction monitoring mode. The method was fully validated with good linearity over the concentration range of 0.098–0.925 ppm of the sitagliptin phosphate monohydrate test concentration for NTTP. The correlation coefficient obtained in each case was >0.998. The recoveries were found to be satisfactory over the range between 80.0 and 120.0% for NTTP. The developed method was able to quantitate NTTP at a concentration level of 0.98 ng mL −1 (0.098 ppm with respect to 10 mg mL −1 sitagliptin phosphate monohydrate).